World Academy of Science, engineering and Technology - Gomes, Natália (2016)
This paper aims to identify how teachers perceive the use of eLearning and Web 2.0 services within the teaching-learning process. The study presents the outcomes from a survey of 129 teachers from four schools of higher education at the Guarda Polytechnic Institute (Portugal). Two main factors associated with the adoption, the intensity of usage of technologies and web 2.0 services are analyzed. Data from teachers confirmed that technologies are an integral part of learning, considering eLearning platforms to be very useful and playing a key role in the whole process. However the usefulness has an insignificant intensity. The inquiry into the need for training revealed that teachers still require help with their digital skills in order to use more technologies in class. As a conclusion, teachers voices warns about the contrariety between having a positive attitude in technology adoption and the actual usage intensity, all of which still demands to institutions for specific training in the effective use of services and in the different phases of the teaching-learning process.